SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN MOBIL MENGGUNAKAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY OF IDEAL SOLUTION (TOPSIS) DI KELIP MOTOR KARANGANYAR - Yulian Tirta Saputra; Sri Hariyati Fitriasih; Setiyowati Setiyowati Setiyowati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
Car is one of the means of transportation that is growing rapidly in the country of Indonesia, because of its comfort and safety. However, problems arise when buyers will buy a car vehicle often faced with a variety of choices of years, types, prices and various other criteria offered. Of the many criteria, buyers have difficulty comparing criteria with other criteria. So, a decision support system was built using the TOPSIS method to rank each alternatif cars based on criteria. The purpose of this study is to build a system of car purchase decision support applications using the TOPSIS method that can provide car recommendations in accordance with the wishes of the buyer. The research method used includes data collection methods and system design methods. The formulation of the problem in this study is how to make car purchasing decisions at Kelip Motor Karanganyar applying the TOPSIS method and how to build an application system for car purchasing decisions by applying the TOPSIS method at Kelip Motor Karanganyar. The result of this research is to build an application system for car purchasing decisions in Kelip Motor Karanganyar using the TOPSIS method.